2017
DOI: 10.3389/fnbeh.2017.00179
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian Extinction and Recovery Effects in Aversive Pavlovian to Instrumental Transfer

Abstract: Three studies explored the sensitivity of aversive Pavlovian to instrumental transfer (PIT) to Pavlovian extinction in rodents. Rats underwent Pavlovian conditioning prior to avoidance training. The PIT test then involved assessment of the effects of the Pavlovian conditioned stimulus (CS) on the performance of the avoidance response (AR). Conducting extinction prior to avoidance training and transfer testing, allowed spontaneous recovery and shock reinstatement of extinguished motivation, whereas conducting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
5
7
1
Order By: Relevance
“…This result is in accordance with a number of studies demonstrating valence-action interactions in the negative domain, as facilitation of avoidance responses have been reported in the presence of aversive stimuli (Campese et al 2017; Dickinson and Pearce 1977). Moreover, our finding matches reports about aversive Pavlovian-to-instrumental transfer (PIT) effects in humans (Geurts et al 2013a; Lally et al 2017; Nord et al 2018; Rigoli et al 2012), where conditioned aversive stimuli decrease operant responses.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in accordance with a number of studies demonstrating valence-action interactions in the negative domain, as facilitation of avoidance responses have been reported in the presence of aversive stimuli (Campese et al 2017; Dickinson and Pearce 1977). Moreover, our finding matches reports about aversive Pavlovian-to-instrumental transfer (PIT) effects in humans (Geurts et al 2013a; Lally et al 2017; Nord et al 2018; Rigoli et al 2012), where conditioned aversive stimuli decrease operant responses.…”
Section: Discussionsupporting
confidence: 92%
“…A shock-paired cue was shown capable of enhancing active avoidance as was a cue paired with a different aversive event, a klaxon horn. While previous studies (Campese et al 2017a) showed that subjects trained to avoid shock demonstrated transfer to a shock paired cue, as well as a klaxon-paired cue, the current findings were observed using a between-subjects design, making it less likely that this result depends on generalization. This is an encouraging step toward using aversive PIT to isolate different forms of aversive motivation (i.e., sensory specific versus general).…”
Section: Discussioncontrasting
confidence: 86%
“…However, there was a significant main effect of stimulus-type, F (1, 45) = 51.754, p < 0.001. Simple contrasts revealed that, as observed in prior work (Campese et al, 2017 ; Fadok et al, 2017 ), rats in general, shuttled more in response to the white noise ( M = 21.033) than they did to tone ( M = 14.7130). Training day also yielded a significant main effect reflecting acquisition of avoidance over this phase, F (4, 180) = 11.372, p < 0.001. Review of Bonferroni-adjusted pairwise comparisons indicate that the number of shuttle responses significantly increased from acquisition training day 1 to training day 5.…”
Section: Resultssupporting
confidence: 72%